Upaya Peningkatan Pengetahuan Remaja tentang Kesehatan Reproduksi dari Sudut Pandang Biologis dan Agama - Aprilia Nuryanti; Rahayu Setyaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Adolescence is a transition period from childhood to adulthood, development as preparation for entering adulthood. Individuals will experience physical, sosial, and psychological/emotional changes, but it is also an excellent opportunity to grow and develop. Adolescents are also at risk of experiencing problems, including reproductive health problems and the development of sexual life. Approaches through biological and religious aspects are an excellent bridge to help adolescents face the changing lives of reproduction and sexuality, which are full of challenges. This activity aims to provide knowledge and foster directed attitudes about reproductive health and sexuality from a scientific and religious perspective. The form of action is counseling. The target of the activity is youth aged 11-15 years, junior high school students totaling 24 accounts (the number of participants is 30 students), and two accompanying teachers. The activity lasted approximately 60 minutes through an online meeting room. The activity evaluation results showed that the level of knowledge of adolescents as measured by online forms was mainly in the excellent range (60%). Students' activeness in interactions during the activity is also a good indicator response to the dimension of a caring attitude towards reproductive health. Suggestions for the following activities are mental health education to deal with hormonal changes resulting in adolescents' cognitive and behavioral changes.